Match or Mismatch? Automatic Admissions and College Preferences of Low- and High-Income Students - Jane Arnold Lincove; Kalena E. Cortes (Institute for the Study of Labor (IZA), 2016)
We examine the role of information in the college matching behavior of low- and high-income students, exploiting a state automatic admissions policy that provides some students with perfect a priori certainty of college admissions. We find that admissions certainty encourages college-ready low-income students to seek more rigorous universities. Low-income students who are less college-ready are not influenced by admissions certainty and are sensitive to college entrance exams scores. Most students also prefer campuses with students of similar race, income, and high school class rank, but only highly-qualified low-income students choose institutions where they have fewer same-race and same-income peers.
Keywords: I21; I23; J15; 330; academic undermatching and overmatching; social matching; admissions policies; Texas Top 10% Plan; automatic admissions